2019
DOI: 10.1161/atvbaha.118.312315
|View full text |Cite
|
Sign up to set email alerts
|

Ponatinib Combined With Rapamycin Causes Regression of Murine Venous Malformation

Abstract: Supplemental Digital Content is available in the text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 51 publications
0
20
0
Order By: Relevance
“…Because recent studies have indicated ponatinib influences vessels, 4,5,11 aortas were examined for evidence of increased reactive oxygen species (ROS) and apoptosis in treated mice by nitrotyrosine and caspase 3 expression, respectively. There was increased nitrotyrosine and caspase 3 expression in the adventitia of mice treated with either 15 or 3 mg/kg of ponatinib ( Figure 1B).…”
Section: Influence Of Ponatinib On Vessel Wall Homeostasismentioning
confidence: 99%
See 1 more Smart Citation
“…Because recent studies have indicated ponatinib influences vessels, 4,5,11 aortas were examined for evidence of increased reactive oxygen species (ROS) and apoptosis in treated mice by nitrotyrosine and caspase 3 expression, respectively. There was increased nitrotyrosine and caspase 3 expression in the adventitia of mice treated with either 15 or 3 mg/kg of ponatinib ( Figure 1B).…”
Section: Influence Of Ponatinib On Vessel Wall Homeostasismentioning
confidence: 99%
“…3 It inhibits ABL1 (T315I), fibroblast growth factor receptors 1 to 4, vascular endothelial growth factor receptors 1 to 3, FLT3, KIT, platelet-derived growth factor receptor, SRC, MEKK3, and Tie2, which are important vascular and myeloid cell receptors involved in cell growth, proliferation, angiogenesis, and repair. [3][4][5] ABL kinases (ABL1 and ABL2) themselves influence vascular development, function, and survival and regulate angiopoietin1/Tie2-mediated activities. 6,7 Loss of ABL1 kinase leads to vascular dysfunction, apoptosis, tissue damage, infarction, and microvascular thrombosis, and its deletion is embryonically lethal.…”
Section: Introductionmentioning
confidence: 99%
“…To overcome imatinib resistance, adenosine triphosphate-competitive ABL kinase inhibitors were developed such as ponatinib, nilotinib, and bosutinib. 9 These drugs improved the efficacy and resistance of imatinib. ABL kinase inhibitor and mTOR are potent compounds decreasing HUVEC TIE2-L914F cell proliferation.…”
Section: Introductionmentioning
confidence: 99%
“…ABL kinase inhibitor and mTOR are potent compounds decreasing HUVEC TIE2-L914F cell proliferation. 9 Ponatinib with rapamycin is a novel targeted therapy to induce regression of venous malformation. 9 In spite of targeted therapy, sclerotherapy remains the easily available management option.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation